Evaluasi Sistem Pelayanan Administrasi Kependudukan Berbasis Elektronik di Dinas Kependudukan dan Pencatatan Sipil Kota Pontianak - Magdalena Depriyani; Vera Aryani; Ika Lusiana Sari (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
This study aims to evaluate the electronic service system at the Department of Population and Civil Registration of Pontianak City. The evaluation is based on five indicators: effectiveness, efficiency, accessibility, user data privacy and security, and public satisfaction and participation. This research uses a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The results show that, in terms of effectiveness, systems such as Pioneers and Siantan have accelerated administrative processes and expanded service coverage. In terms of efficiency, these systems have reduced physical queues and shortened service times, although limited daily quotas remain a constraint. Regarding accessibility, digital literacy gaps—especially in certain areas still hinder some citizens from utilizing electronic services. User privacy and data security are maintained through collaboration with the Communications and Information Agency (Kominfo) and the implementation of security testing. Meanwhile, overall public satisfaction is relatively high, despite complaints about network access and limited service hours. Community participation is also actively seen, including initiatives to assist other residents in using online services. In conclusion, Disdukcapil’s electronic services have shown positive development, but improvements are still needed in technical infrastructure, digital literacy, and system strengthening to ensure inclusive and sustainable service delivery.